Stability of a rotor excited by parameter and bedded on two radial bearings. - Hai, Nguyen (Vietnam Journal of Mechanics, 1982)
The paper deals with the question of stability of a rotor bedded on two radial bearings, where the effect of the oil film has been taken into consideration.